Suspension surgery with autogenous fascia lata via a less invasive modification of the Crawford method on 85 patients with congenital severe eyelid ptosis. Issue 4 (August 2015) - Krohn-Hansen, Dag; Haaskjold, Erling; Nicolaissen, Bjørn
Abstract Background. Autogenous fascia lata is considered the gold standard for frontalis suspension surgery to correct severe congenital upper eyelid ptosis. Methods. This study evaluated the efficacy of a less invasive modification of the standard technique described by Crawford. A total of 85 patients with severe congenital ptosis were enrolled in this study and submitted to surgical correction by frontalis suspension using autogenous fascia lata. Among these patients, 51 had previously undergone ptosis correction using other surgical techniques. The final lid level and contour were evaluated in addition to complications, such as lagophthalmos and ptosis recurrences. Results. Overall, the final results were evaluated as good in 71 of the cases, whereas 11 cases were graded as satisfactory and three cases as poor according to the success criteria. The average increase in eyelid height, measured as the marginal reflex distance (MRD), was 2.9 mm. The best results were obtained in the group of patients with no previous eyelid surgeries. The examples of poor results could be attributed to lagophthalmos and were all confined to the group of patients with a previously failed surgery that employed synthetic suspension materials and levator shortening procedures. No recurrences were observed during the follow-up interval, which lasted an average of 6.4 months (range = 2–59 months). Conclusions. This technique allows a safe surgery with an overall high rate of success. This surgery is also safe and successful in cases of congenital ptosis with associated abnormalities, such as blepharophimosis, and in cases that require secondary ptosis repair.